Os significantes da escuta psicanalítica na clínica comtemporânea - Mendes, Elzilaine Domingues (2005)
The objective of this work is to circumscribe the destinies of the psychoanalytical listening in the contemporary clinic. When giving heard to hysterical, Freud breaks up with the medical model of treatment and inaugurates a differentiated clinical practice, in the which the patient leaves of being examined and he is invited to narrate his suffering, becoming subject in his cure process. Thus, psychoanalytical listening opens new horizons for the understanding of the man and the world where we live. However, today we came across with symptoms such as syndrome of the panic, depressions, psychosomatic diseases, compulsions, and school failure, that differ of the presented by Freud's patients. So, we started to question our clinical practice: How do the social and cultural changes interfere in the human subjectivity? What is there in common in the contemporary pathologies? Which are the contributions of the psychoanalysis to understand the world where we live? Which is the destiny of the psychoanalytical listening due to so many transformations? Departing from these questionings, we analyze how the psychoanalytical listening appeared and in which social and cultural context Freud was inserted. We compared the Freudian age with the contemporary clinic. We verify together with Lipovetsky and Forbes that there was a change from the industrialized age that Forbes calls "father-guided to the globalized one. For Lipovetsky, the progress of the individuality and the decline of the organizing power, that the collectivity had on the individual, weakened the personalities. The contemporary individual is more autonomous, because he has greater freedom of choices. However, he finishes for becoming more fragile in function of the amount of demands and obligations that our world imposes on him. In agreement with Costa, in modernity, the man looked for the ideal of perfection through the feelings. Nowadays, our society gives a great emphasis to the corporal image. The man looks for a perfect image of himself and he suffers of a fascination for the possibilities of physical transformation offered by the prostheses, plastic surgeries, medicines and physical exercises. The self-valorization of the world of the images and of the individualism, allied to the excessive volume of information, substitutes the exchange of experiences causing the impoverishment of the interior life. The individual cannot express his feelings, attributing all his evils to a causality inscribed in the body. The narrative becomes substituted by the action. In this context, the analyst must recognize that the patients' sufferings are related to his corporal image. Besides, the analyst have to understand the transformations of our world and to enlarge his/her psychoanalytical listening, creating deeper and wide forms of intervention, with a bigger flexibility and diversity, allowing that psychoanalysis supports a larger number of practices, important to others, and different, settings beyond the private clinic.